The effect of changes (time, profession, etc.) on the position of women entrepreneur - Tavakol, Nasim (Revista Publicando, 2018)
Introduction: in the developed countries, paying attention to women’s job has been always considered by planners to realize social development. Purpose: this study has investigated the effect of changes created (time, profession, etc.) on position of women entrepreneur in Comprehensive Center for Women and Family Empowerment and Entrepreneurship. Method: statistical population of this study consists of managers, experts and women entrepreneur in Comprehensive Center for Women and Family Empowerment and Entrepreneurship. The size of population is infinite. Using sampling method and according to Krejcie-Morgan table, a minimum number of 384 people are introduced for the study and about 215 users responded. The method applied in this study is descriptive-survey method in kind of applied research and correlation. Required data was collected and was classified in Excel file as reference data. Moreover, the hypotheses are tested using LISREL equation structure software. Results: obtained results showed that professional positions (job and learning) of the current age can affect position of women entrepreneur according to traditional methods of entrepreneurship, knowledge and the knowledge development in a growing business, meeting personal needs of women and promotion of use of information communication technology (ICT) to facilitate affairs.